1996
DOI: 10.3354/dao024205
|View full text |Cite
|
Sign up to set email alerts
|

Variations in biochemical composition of juvenile Ruditapes philippinarum infected by a Vibrio sp.

Abstract: The biochemical composition of young Rudltapes phlllppinaruln was exanlined in 2 groups of clams, healthy clams and those expenmentally Infected with the pathogenic V~b n o P1 bactenum to document utilization of biochemical reserves in ~n d~v i d u a l s affected by 'brown ring d~s e a s e ' After 1 mo of starvation, refeedlng half of the expenmental clams induced recovery as determined by the absence of v~s u a l slgns of disease D~s e a s e was associated with decreased dry weights In both fed and starved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 11 publications
4
24
0
Order By: Relevance
“…These winter mortalities were subsequently attributed to BRD (Paillard, 1992). Our results also confirm the observations of Plana (1995) and Plana et al (1996), who showed that Manila clams experimentally infected by Vibrio tapetis showed a significant decrease in dry weight and glycogen reserves in comparison to uninfected individuals. In marine bivalves, weight loss associated with microparasite infection is a general pattern.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…These winter mortalities were subsequently attributed to BRD (Paillard, 1992). Our results also confirm the observations of Plana (1995) and Plana et al (1996), who showed that Manila clams experimentally infected by Vibrio tapetis showed a significant decrease in dry weight and glycogen reserves in comparison to uninfected individuals. In marine bivalves, weight loss associated with microparasite infection is a general pattern.…”
Section: Discussionsupporting
confidence: 82%
“…This value may be overestimated because growth rate value was obtained at 18 • C, temperature which is near to the thermal growth optimum of V. tapetis (Haberkorn, 2005). This rough estimate allows us to conclude that the host energy loss due to the V. tapetis population growth is very low and can not explain the weight loss and reserve depletion observed by Plana et al (1996) and Plana (1995). Choi et al (1989) showed that, for heavily infected oysters Crassotrea virginica, the protozoan parasite P. marinus consumes more energy than the oyster has available after meeting its own metabolic needs.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Nevertheless, oysters infected by Vibrio splendidus had a lower level of carbohydrate than oysters free of both pathogens and oysters infected by herpesvirus alone (Table 4). Similarly, young clams Ruditapes philippinarum infected by the pathogen V. tapetis showed a significant decrease in glycogen compared with healthy clams (Plana et al 1996). However, it is still unclear why the level of carbohydrate in oysters co-infected by V. splendidus and herpesvirus was similar to that of oysters free of these 2 pathogens (Table 4).…”
Section: Relationships Between Oyster Mortalities Pathogens and Enermentioning
confidence: 90%